2017
DOI: 10.3390/ma10121405
|View full text |Cite
|
Sign up to set email alerts
|

Novel Development of Phosphate Treated Porous Hydroxyapatite

Abstract: Phosphoric acid-etching treatment to the hydroxyapatite (HA) surface can modify the solubility calcium structure. The aim of the present study was to develop phosphate treated porous HA, and the characteristic structures and stimulation abilities of bone formation were evaluated to determine its suitability as a new type of bone graft material. Although the phosphoric acid-etching treatment did not alter the three-dimensional structure, a micrometer-scale rough surface topography was created on the porous HA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…It is well known that HA is a biomaterial relatively insoluble in vivo. By contrast, β-TCP shows good bioreabsorption in vivo [32]. With the purpose of granting a certain degree of biodegradation to the 3D structures and trying to adjust the kinetics of biodegradation to the rate of formation of new bone without abrupt deterioration of the final mechanical properties of the scaffolds, several 40 wt.% of biphasic HA/β-TCP systems were also prepared.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that HA is a biomaterial relatively insoluble in vivo. By contrast, β-TCP shows good bioreabsorption in vivo [32]. With the purpose of granting a certain degree of biodegradation to the 3D structures and trying to adjust the kinetics of biodegradation to the rate of formation of new bone without abrupt deterioration of the final mechanical properties of the scaffolds, several 40 wt.% of biphasic HA/β-TCP systems were also prepared.…”
Section: Resultsmentioning
confidence: 99%
“…Although the porous structures and rough surfaces of the scaffolds resulted in a relatively lower degree of crystallinity (DC), the DC of EDHA (20%) was still higher than that of PSHA (12%). Previous studies have shown that HA with higher DC has lower solubility ( Doi et al, 2017 ; Bertazzo et al, 2010 ; Kattimani et al, 2016 ; da Silva et al, 2020 ), indicating that the solubility of HA coated in PSHA is higher than that of EDHA in the present study. HA coated on EDHA scaffolds completely covered the scaffolds, while molten PSHA coatings were relatively smooth and evenly spread on the scaffold surface.…”
Section: Discussionmentioning
confidence: 46%
“…Bioceramics based on HA are biocompatible, corrosion-resistant, have low toxicity, and have good compressive strength [40]. Whereas β-TCP is bioabsorbable, and bioresorption occurs due to osteoclast activity [41]. An example of porous hydroxyapatite is shown in Figure 1 [42].…”
Section: Methodsmentioning
confidence: 99%